Sonographic findings of hepatic venous gas in association with spontaneous rupture of a Klebsiella pneumoniae liver abscess: a case report. Issue 3 (March 2021) - Zheng, Haining; Gu, Chenxing; Jiang, Suzhen; Liu, Xiaona; Wang, Xiaoqing; Wen, Chaoyang
Hepatic venous gas (HVG) is a very rare ultrasonic finding, and it is defined as abnormal accumulation of gas in the hepatic venous system. Various diseases can cause HVG, and femoral venous catheter is the most common cause. We, herein, present the case of a 79-year-old female patient with HVG that was caused by spontaneous rupture of a Klebsiella pneumoniae liver abscess. This was first found by bedside ultrasonography. On the basis of the blood culture results, imipenem–cilastatin and cefoperazone sulbactam were administered and the effect was acceptable. After 41 days of antibacterial and symptomatic treatment in the hospital, the patient had recovered well and was discharged. All of the previous reports on HVG have been summarized by thoroughly reviewing the previous published work. Overall, this is the first patient with HVG in association with spontaneous rupture of a K. pneumoniae liver abscess, and it might provide insights for future studies regarding the treatment of this disease.